Evaluation of Antibiotic Utilization Patterns in Community-Acquired Pneumonia Inpatients Using ATC/DDD and DU 90% Methods at Taman Husada Bontang Regional General Hospital in 2024 - Lawin, Handratin; Geografi, Liniati (MEDFARM: Jurnal Farmasi dan Kesehatan, 2025)
Community-acquired pneumonia (CAP) represents an acute infectious inflammatory condition affecting the lung parenchyma, typically contracted in non-hospital settings. Antibiotic therapy serves as the primary treatment modality for CAP. This investigation employs a dual methodological approach: quantitative assessment through the Defined Daily Dose (DDD) metric and qualitative evaluation utilizing the Drug Utilization 90% (DU 90%) analysis. The study objectives focus on characterizing antibiotic consumption patterns among CAP patients at Taman Husada Bontang Regional General Hospital during 2024, employing both ATC/DDD and DU90% analytical frameworks. This quantitative descriptive research utilized retrospective data collection from medical records of CAP inpatients admitted between January and June 2024. Following comprehensive screening, 83 eligible patient records were included for analysis. Data processing involved descriptive statistical methods with Microsoft Excel for tabular presentation of findings. Demographic analysis revealed a homogeneous age distribution (100% within 18-39 years) with male predominance (59%). Quantitative evaluation identified Ceftriaxone as the most frequently prescribed antibiotic (42.5 DDD/100 treatment days). The DU 90% analysis further delineated the therapeutic landscape, with Ceftriaxone (52.9%), Levofloxacin (23.5%), Azithromycin (11.1%), and Ceftazidime (5.3%) constituting the predominant therapeutic agents.